Viral subtype and heterosexual acquisition of HIV infections diagnosed in Scotland. Issue 6 (1st December 1999) - Yirrell, D L; Goldberg, D J; Whitelaw, J; McSharry, C; Raeside, F; Codere, G
Abstract : OBJECTIVE: As at December 1998, 87% of the estimated 33 million people living with HIV throughout the world resided in Africa and South East Asia. In Scotland (and the United Kingdom), a major public health concern has been that non-B subtypes of HIV which predominate in the regions above might enter the country and spread heterosexually among the indigenous population. The authors conducted an investigation to determine if, and to what extent, such transmission had occurred. METHODS: Stored blood samples from people who were diagnosed as HIV positive in central Scotland during 1995-7 and who were reported to have acquired their infection heterosexually, were identified. Sequence data were sought from each sample and, where obtained, viral subtype was assigned. For each case, viral subtype was linked to corresponding epidemiological details on heterosexual risk. RESULTS: Viral sequence was obtained from specimens for 53 of 59 cases. For 43 of the 53 cases, information on region of sexual contact was known. All 19 cases who had a sexual risk in Africa or Asia had a non-B subtype (A, C, or E) while 20 of 24 cases who did not report sexual contact in these regions had a B subtype (p < 0.0001). Of the remaining 10 cases, nine had a subtype B and one a subtype C virus. CONCLUSION: There is no evidence that non-B viral strains from developing countries have yet disseminated appreciably among indigenous heterosexual men and women within Scotland. Continuing to collect both demographic and molecular data from indigenous heterosexuals who are newly diagnosed with HIV would improve the chances of detecting rapidly any appreciable dissemination of non-B subtypes among this population if it were to occur. Such information would be helpful in informing HIV prevention strategies.